Introduction: form and content, philosophy and literature - Nussbaum, Martha; von der Walde, Erna (Estudios de Filosofía, 1995)
Both philosophy and literature in as much as they represent a search for truth, for answers to a whole range of vital questions each turn to a formal structure which of necessity is the expression of an attitude to life. Literary form cannot be separated from philosophical content, since it is the result of an enquiry which strives to provide answers to certain matters of human existence. In much the same way, its philosophical content is grafted in its expression into a formal structure which transmits a meaning of life. Form and content may not be split up without fracturing the vision of life that both literary and philosophical texts afford. Nevertheless, certain questions beg the asking: How to write? What forms, structures and language are we to use to speak of such particular issues as love? To what extent may we write philosophically upon life and its own special questions? What contributions has literature made in the search of alternative visions on human experience? This is the point of departure for this essay which aims to grant literature and its means of expression a more central role in the field of reflection on the meaning of life and other important questions on human concerns.